1980
DOI: 10.2307/3808354
|View full text |Cite
|
Sign up to set email alerts
|

Spring and Summer Foods of Deer in the Missouri Ozarks

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. This content downloaded from 165.95.226.100 on Thu, 08 Oct 2015 21:34:33 UTC All use subject to JSTOR Terms and Conditions Abstract: A 3-year investigation was conducted to asc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 2 publications
2
13
0
Order By: Relevance
“…In this study different methods of analysis gave variable results, as previously reported (Korschgen et al, 1980;Rogers et al, 1981; and others). None of the methods is unbiased, and none can be safely assumed to represent the actual diet consumed by the animal.…”
Section: Coblentz (1970) Reported a Significant Correlation Between Psupporting
confidence: 80%
“…In this study different methods of analysis gave variable results, as previously reported (Korschgen et al, 1980;Rogers et al, 1981; and others). None of the methods is unbiased, and none can be safely assumed to represent the actual diet consumed by the animal.…”
Section: Coblentz (1970) Reported a Significant Correlation Between Psupporting
confidence: 80%
“…Mushrooms were consumed mostly in spring in HD and in fall in LD, which may be explained by different seasonal availability or by the possibility that White-tailed Deer feed on them when preferred foods are rare at both ends of the growing season. Many studies reported large amounts of mushrooms in White-tailed Deer diet (Crawford 1982;Johnson et al 1995;Korschgen et al 1980;McCaffery et al 1974), but nobody has yet considered the potential impact of deer herbivory on mushrooms.…”
Section: Discussionmentioning
confidence: 99%
“…Food items which dominated in LD diets remained almost absent from HD rumens. For instance Liliacae, such as Yellow Clintonia and Wild-Lily-of-the-Valley, which White-tailed Deer normally consume in the Northeast (Crawford 1982;Korschgen et al 1980;McCaffery et al 1974;Skinner and Telfer 1974;Waller and Alverson 1997) occupied a marginal volume in HD rumens. Liliacae are particularly vulnerable to deer browsing Waller and Alverson 1997) and can be used as indicators to estimate the impact of White-tailed Deer on plant communities (Balgooyen and Waller 1995).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations